2009
DOI: 10.1091/mbc.e08-11-1109
|View full text |Cite
|
Sign up to set email alerts
|

PUMA Promotes Bax Translocation by Both Directly Interacting with Bax and by Competitive Binding to Bcl-XL during UV-induced Apoptosis

Abstract: Cell apoptosis induced by UV irradiation is a highly complex process in which different molecular signaling pathways are involved. p53 up-regulated modulator of apoptosis (PUMA) has been proposed as an important regulator in UV irradiation-induced apoptosis. However, the molecular mechanism through which PUMA regulates apoptosis, especially how PUMA activates Bcl-2-associated X protein (Bax) in response to UV irradiation is still controversial. In this study, by using real-time single-cell analysis and fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 53 publications
(95 reference statements)
6
78
0
Order By: Relevance
“…This is consistent with the finding that Puma can bind with high affinity and therefore neutralise all pro-survival Bcl-2 family members, whereas Noxa interacts only with Mcl-1 and A1 [88,101,102]. Another reason why Puma may be a more potent killer than Noxa is provided by several studies, which showed that only the former is able to bind to and directly activate Bax [86,87,103,104].…”
Section: Apoptosissupporting
confidence: 87%
“…This is consistent with the finding that Puma can bind with high affinity and therefore neutralise all pro-survival Bcl-2 family members, whereas Noxa interacts only with Mcl-1 and A1 [88,101,102]. Another reason why Puma may be a more potent killer than Noxa is provided by several studies, which showed that only the former is able to bind to and directly activate Bax [86,87,103,104].…”
Section: Apoptosissupporting
confidence: 87%
“…Puma induces apoptosis by binding and antagonizing all of the 5 pro-survival Bcl-2 family members or, possibly more controversially, by directly activating the proapoptotic multi-BH domain protein Bax. [37][38][39][40][41][42] The proapoptotic effect of Puma might therefore be counteracted by one or several antiapoptotic proteins of the Bcl-2 family. Mcl-1 is an outstanding candidate for this role because it has recently been shown to be critical for the formation and of the germinal center reaction and establishment of B-cell memory.…”
Section: Discussionmentioning
confidence: 99%
“…Puma may also directly interact with Bax, promoting its mitochondrial translocation (Chipuk et. al., 2004;Zhang et. al., 2009).…”
Section: Protein Aggregates and Cell Deathmentioning
confidence: 99%
“…The Puma/Bax dependent pathway is usually triggered by a variety of cellular stress such as heat shock and oxygen stress (Uo et. al., 2007;Zhang et. al., 2009).…”
Section: Protein Aggregates and Cell Deathmentioning
confidence: 99%